Effect of High Volume Strength Training on Measures of Physical Performance among amateur athletes (International Journal of Food and Nutritional Sciences, 2022)
The objective of the study was to find out the effect of high volume strength training on selectedmeasures of physical performance. A total of 20 male amateur athletes were selected as subjectsfor the study age ranging from 25 to 35 years. All the selected subjects were equally dividedinto two group – experimental group and control group. The experimental group underwent sixweeks of high volume strength training while the control group was not any sort of trainingduring the intervention period. The data of four measures of physical performance – maximumstrength (1-Repetition Maximum), explosive strength (standing broad jump), speed (30-msprint), and agility (modified agility T-test), was collected before and after the completion oftraining. Descriptive statistics and paired t-test was used to analyse the collected data. Theresult showed that high volume strength training is significantly effective in improving themeasures of physical performance taken in the study.